Implementation of the Financial Inclusion Concept in the Zakat Payment System at BAZNAS Kampar Regency - Mifta Hasda; Saru Reza; Muhammad Arif; Binda Rahma Cahyani (Global Sustainability Research Institute, 2025)
Introduction:This study explores the implementation of inclusive zakat payment systems at the National Zakat Agency (BAZNAS) in Kampar Regency. Inclusive zakat payment aims to provide broader and easier access for muzakki (zakat payers) in fulfilling their zakat obligations, both through direct and digital channels. This initiative supports financial inclusion by integrating zakat management into accessible and innovative financial services. Methods:The research employed a qualitative approach. Data were obtained through interviews with key informants, including BAZNAS leaders in Kampar Regency, as well as secondary data from relevant literature, reports, and official documents. data analysis using the Miles and Huberman 1994 approach. The analysis focused on understanding the implementation process, accessibility, and service quality of zakat payment mechanisms. Results:The findings indicate that zakat payment access in Kampar Regency is relatively easy and affordable. Muzakki can pay zakat directly at the BAZNAS office, through nearby UPZ (Zakat Units), or via digital platforms. BAZNAS offers various zakat products tailored to the needs of the payers. Additionally, the competence and service quality of amil (zakat officers) are crucial factors influencing effective implementation. The inclusive approach has also contributed to an increase in the total amount of zakat collected in the region. Conclusion and Suggestion: The implementation of inclusive zakat payments at BAZNAS Kampar has successfully expanded access and improved the efficiency of zakat collection. To sustain and enhance these outcomes, BAZNAS is encouraged to continuously develop digital payment innovations, strengthen amil training, and promote public awareness campaigns about the benefits of zakat inclusion.